How does carbon dioxide permeate cell membranes? A discussion of concepts, results and methods - Endeward, Volker; Al-Samir, Samer; Itel, Fabian; Gros, Gerolf (Frontiers in Physiology, 2014)
We review briefly how the thinking about the permeation of gases, especially CO2, across cell and artificial lipid membranes has evolved during the last hundred years. We then describe how the recent finding of a drastic effect of cholesterol on CO2 permeability of both biological and artificial membranes fundamentally alters the long-standing idea that CO2 – as well as other gases – permeates all membranes with great ease. This requires revision of the widely accepted paradigm that membranes never offer a serious diffusion resistance to CO2 or other gases. Earlier observations of "CO2-impermeable membranes" can now be explained by the high cholesterol content of some membranes. Thus, cholesterol is a membrane component that nature can use to adapt membrane CO2 permeability to the functional needs of the cell. Since cholesterol serves many other cellular functions, it cannot be reduced indefinitely. We show, however, that cells that possess a high metabolic rate and/or a high rate of O2 and CO2 exchange, do require very high CO2 permeabilities that may not be achievable merely by reduction of membrane cholesterol. The article then discusses the alternative possibility of raising the CO2 permeability of a membrane by incorporating protein CO2 channels. The highly controversial issue of gas and CO2 channels is systematically and critically reviewed. It is concluded that a majority of the results considered to be reliable, is in favour of the concept of existence and functional relevance of protein gas channels. The effect of intracellular carbonic anhydrase, which has recently been proposed as an alternative mechanism to a membrane CO2 channel, is analysed quantitatively and the idea considered untenable. After a brief review of the knowledge on permeation of O2 and NO through membranes, we present a summary of the 18O method used to measure the CO2 permeability of membranes and discuss quantitatively critical questions that may be addressed to this method.